Research on the effect of green credit on ecological welfare performance: Evidence from China - Zhang, Ran; Cao, Yahui; Wu, Kerong; Sun, Huaping (Frontiers in Environmental Science, 2022)
Achieving high-quality economic development is crucial feature of China's new development stage. As an environmental regulation tool by implementing differentiated credit policy, green credit is an inevitable choice to achieve high-quality economic development. In this paper, ecological welfare performance (EWP) is used to measure the level of high-quality economic development. And based on the panel data of 30 provinces during 2008-2019, the spatial Durbin model and mediating effect model are used to empirically study the direct and indirect effect of green credit on EWP in China. The results show that: 1) China's EWP shows positive spatial correlation in the global spatial scope, with local characteristics of high-high aggregation and low-low aggregation. 2) Green credit can significantly promote the EWP of local region, but has negative spatial spillover effect on the EWP of adjacent regions. 3) Green credit can promote EWP by improving technological innovation, industrial structure upgrading, energy consumption structure. Based on these conclusions, the policy recommendations are put forward.